Traumatic J-Pouch Perforation following a Blunt Abdominal Injury - Leonid Drober; David Hochstein; Hany Bahouth (Case Reports in Surgery)
A 46-year-old male was admitted to the trauma department after a motor vehicle accident. He presented with severe abdominal pain and a distended abdomen with peritonitis. His past surgical history included total proctocolectomy with ileal J-pouch anal anastomosis for ulcerative colitis 20 years previously. Computed tomography showed free peritoneal air and fluid in the abdomen mandating an exploratory laparotomy. A perforation at the ileal J-pouch blind end was found. Primary closure with diverting loop ileostomy was performed. The patient had an uneventful recovery and underwent closure of the ileostomy two months later. The case and management are discussed after reviewing the literature.